Analisis Geologi Struktural untuk Mengevaluasi Potensi Gempa Bumi di Wilayah Tertentu - Hasan, Haslinda (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This study aims to conduct structural geological analysis to evaluate the potential for earthquakes in certain areas. The methods used include field surveys, geological modeling, structural analysis, and mapping of earthquake potential zones. The results of this study will provide better insight into the potential earthquake risk in the region and can be used in disaster mitigation planning. In addition, the study also applied modern seismic monitoring technologies, including the use of seismometers and seismic data processing to monitor current earthquake activity. The collected seismic data has helped in a deeper understanding of the behavior of potential earthquake zones, including the frequency, magnitude, and energy released by previous earthquakes. The results of this monitoring provide valuable insights in mitigating earthquake risk by improving early warning and emergency response planning. By combining structural geological analysis and seismic monitoring, the study makes a significant contribution in understanding and managing earthquake potential in the region holistically.